The Influence of Audit Transparency, Minor Findings, and Arrogance on Auditee Satisfaction - Ricky Bryan D.P. Tampubolon (GLOBAL SCIENTS PUBLISHER, 2026)
Internal audit plays a crucial role in ensuring accountability and effective governance within organizations. One of the key indicators of audit effectiveness is auditee satisfaction, which reflects the extent to which the audit process meets auditee expectations. This study aims to examine the influence of audit transparency, minor findings, and auditor arrogance on auditee satisfaction. Using a quantitative approach, data were collected through a structured questionnaire distributed to 153 auditees working in private companies in Jakarta. The data were analyzed using multiple linear regression with SPSS software. The findings reveal three main results. First, audit transparency has a positive and significant effect on auditee satisfaction, suggesting that open communication and clear disclosure of audit processes enhance auditee trust and comfort. Second, minor findings have a negative and significant impact on auditee satisfaction, indicating that excessive emphasis on trivial issues may reduce the perceived value of audit services. Third, auditor arrogance shows a negative but statistically insignificant relationship with auditee satisfaction, implying that auditees tend to prioritize audit professionalism and technical quality over personal attitudes. The study concludes that maintaining audit transparency and avoiding excessive focus on minor findings are essential to sustaining auditee satisfaction. The research is limited by its scope, as respondents were only drawn from private companies in Jakarta. Future studies are encouraged to include broader samples across industries and regions, as well as additional factors such as auditor competence and communication quality. This study contributes to both theory and practice by highlighting the importance of balancing technical and relational aspects in internal auditing.